Evaluating the spatial and temporal variation in baseflow across headwater streams in the Jonkershoek valley, South Africa - R. A. Mokua; J. Glenday; D. Mazvimavi (Proceedings of the International Association of Hydrological Sciences, 2024)
An understanding of processes and factors accounting for spatiotemporal variations in baseflow is necessary for sustainable water resources management, particularly in semi-arid regions. This study assessed the spatial and temporal variations in baseflow across three mountain streams within the Jonkershoek valley, in the Table Mountain Group (TMG) geological region of South Africa. A two-parameter recursive digital filtering method (RDF) was combined with conductivity mass balance (CMB) using electrical conductivity to separate baseflow from daily streamflows during the 1946–2019 period. The results indicated that annual baseflow contributions varied spatially. Baseflows were estimated to contribute 38 % to 86 % of the annual streamflows across the three sub-catchments. This notable variation could be explained by differences in topography, geology and fracturing, and vegetation cover. All three sub-catchments had higher proportional contributions from baseflow in the dry summer compared to the wet winter, while interannual variations were relatively minor.